Information Retrieval System Herbal Plant (Information Technology and Telematics, 2016)
ABSTRACT The design of information retrieval system (STKI) with Vector Space Model method (VSM) is to allow users to search for Herbal Plant quickly and accurately. VSM method gives a different similarity value for each document stored in the database, where the documents with the highest similarity value is placed at the very top of the search results.Herbs can be processed into a useful drug. This thing we need to learn about herbs because herbs is very useful for natural healing.therefore constructing an information retrieval system herbal platwho can help facilitate the public to get to know and know how to make the medicine with herbal plant material. Keywords: Information Retrieval System, Herbal Plant